Spatial electric load forecasting - Willis, H. Lee (Electrical engineering and electronics, 1996)
Surveys the theory and methods needed to predict the future requirements for electric T&D systems. The text offers discussions of analytical techniques and computer programs, and contains practical worked-out problems to illustrate key points. It also features full details on the load forecasting environment.